DESIGN OF ENGINE ROLL MOUNT - Kumar, K.N Arun; Rajan, A.S.; S Shreedharan M.D, Jeyakrishnan.; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
Rear roll mount is one of the mountings used to support engine in an engine room as well as to isolate the vibration and excitation between the engine assembly and the vehicle body. A rear room mounting is designed in stages and was performed analysis to get the improved 1st mode shape of the natural frequency by using Msc Nastran. The base design is made in such a way that it appears as a simple jointed panels to form mounting. The design is iterated several times until it gives the value of more than 200 Hz for the st mode shape. The design changes include the addition of weld point and bolt mounting as well as panel’s extension. Thickness of the design is also changed to around 3 mm to improve the rigidity. The final design incorporates a better characteristic that it gives an improvement of 36% increase in 1st natural frequency.